Telomere length in individuals with and without major depression and adverse childhood experiences. (August 2022) - Kuehl, L.K.; de Punder, K.; Deuter, C.E.; Martens, D.S.; Heim, C.; Otte, C.; Wingenfeld, K.; Entringer, S.
Abstract: Major depressive disorder (MDD) and adverse childhood experiences (ACE) are associated with poor physical and mental health in adulthood. One underlying mechanism might be accelerated cellular aging. For example, both conditions, MDD and ACE, have been related to a biological marker of cellular aging, accelerated shortening of telomere length (TL). Since MDD and ACE are confounded in many studies, we aimed with the current study to further disentangle the effects of MDD and ACE on TL using a full-factorial design including four carefully diagnosed groups of healthy participants and MDD patients with and without ACE (total N = 90, all without use of antidepressants). As dependent variable, TL was assessed in leukocytes. We found no group differences based on MDD and ACE exposure in TL. While TL was negatively associated with age and male sex, TL was not associated with any measure of severity of MDD, ACE or current stress. One possible explanation for our null result may be the comparatively good physical health status of our sample. Future research is needed to elucidate the relation of TL, MDD and ACE, taking potential effect modification by medication intake and physical health status into account. Highlights: Healthy and depressed individuals with and without childhood trauma were tested. The sample had a good physical health status and no use of antidepressants. Telomere length (TL) of leukocytes did not differ between groups. TL was not associated with severity of depression or childhood trauma. TL was not associated with subjective current stress.